2015
DOI: 10.1097/qad.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

High completion of isoniazid preventive therapy among HIV-infected children and adults in Kinshasa, Democratic Republic of Congo

Abstract: We assessed isoniazid preventive therapy (IPT) completion and predictors among HIV-infected children and adults in two HIV clinics in Kinshasa, Democratic Republic of Congo. Between September 1, 2012 and June 15, 2013, 546 children (1–15 years) and 1532 adults (> 15 years) were initiated on IPT; 86.6% (408/470) of children and 88.2% (1129/1280) of adults with an IPT outcome completed their therapy. Patients on ART at IPT initiation were more likely to complete IPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
4
11
3
Order By: Relevance
“…Though the majority of patients in our study completed IPT, there remains room for improvement especially among younger patients and those reporting side effects. Although prior research has shown that patients on ART are more likely to adhere to IPT, 8,9 our findings suggest that in a sample of highly ART adherent patients in differentiated care, barriers to IPT completion persist.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Though the majority of patients in our study completed IPT, there remains room for improvement especially among younger patients and those reporting side effects. Although prior research has shown that patients on ART are more likely to adhere to IPT, 8,9 our findings suggest that in a sample of highly ART adherent patients in differentiated care, barriers to IPT completion persist.…”
Section: Discussioncontrasting
confidence: 68%
“…In the Democratic Republic of Congo and Ethiopia IPT completion among patients on ART was 89% 8 and 86%, 9 respectively. One possible explanation for this difference is that some patients in differentiated care may perceive the costs associated with increased visit frequency for IPT to outweigh the benefits of IPT, and they in turn may prioritize collecting ART over IPT refills.…”
Section: Discussionmentioning
confidence: 98%
“…WHO recommends the completion of at least six months IPT for the successful prevention of active tuberculosis among PLHIV (4,10). Globally, six-month IPT completion has been reported to range from 39-99% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and in Tanzania studies reported 65%-98% of those who initiated IPT, completed the six month treatment course (6,20,(38)(39)(40). Most epidemiological studies have shown that IPT completion reduces the risks of mortality among PLHIV (8,26,41)…”
Section: Introductionmentioning
confidence: 99%
“…Our IPT completion and adherence rates were similar to reports from other African studies with findings ranging from of 78–98.9 %. 12, 13, 17, 19, 3133 We attributed high IPT adherence to the well-resourced clinical research setting, structured adherence support programme and needing to come in for ART. There is strong evidence supporting combining ART use with IPT to significantly improve IPT adherence.…”
Section: Discussionmentioning
confidence: 99%